Gaya Kepemimpinan Kepala Sekolah pada Abad 21: Analisis Literatur terhadap Implikasi terhadap Kinerja Guru - Ivon Mukaddamah (Hikamatzu | Journal of Multidisciplinary, 2025)
This literature analysis explores the leadership styles of school principals in the 21st century and their implications for teacher performance. The study highlights the significance of adaptive, participative, and transformational leadership approaches in addressing contemporary educational challenges. Principals who embrace a visionary and collaborative leadership style, integrated with technology and innovation, have been shown to positively influence teacher motivation, professionalism, and overall performance. Furthermore, effective communication and supportive leadership foster a conducive working environment, encouraging continuous professional development and enhancing educational quality. The findings emphasize the critical role of modern leadership in shaping effective teaching practices and improving school outcomes.